Confrontation of Translators in Transferring Facts into Russian Translation of the Epic of Narts (Based on the Translation by A. A. Dzantiev, T.A. Hamitsaeva) - Maryam Shafaghi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The epic of Narts is based on the folklore of the Ossetian and the causes of its people’s pride. In this research, the equivalent of cultural and historical names and facts in the Russian translation of the text by A. A. Dzantiev and T. A. Hamitsaeva have been studied. Changing the writing alphabet of Ossetian language to Cyrillic in 1954 caused phonetic changes, especially in the specific names of the Ossetian. Both translators are Ossetian and fluent in the Russian language. They have tried in many cases to keep the fact in their own language. In the text of the translation, we see that even the equivalent words have been preserved in the original language of the text due to the cultural burden and the importance of the age and social hierarchy in that culture. The sounds are entirely in the Ossetian translation text. In translating proverbs, although in some cases translators rely on Russian equivalents, there are also examples of word-for-word translation. In translating units of measurement, translators used obsolete Russian words.